PENGARUH TEMPAT PENYIMPANAN DI APOTEK TERHADAP KADAR VITAMIN C DALAM SEDIAAN TABLET - Yohana Mitta Puspitasari; Erlien Dwi Cahyani; Leo Eladisa Ganjari (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2023)
Vitamin C is an unstable in storage. The stability of vitamin C is influenced by many factors such as temperature, pH, sunlight and the presence of heavy metals such as iron and copper. The purpose of this study was to determine differences in vitamin C levels in tablets based on storage areas with different lighting conditions at a pharmacy in Madiun. In this study, samples of vitamin C tablets were stored on the front shelf facing the entrance of the pharmacy which was exposed to indirect sunlight, the upper shelf which was exposed to the light, and the lower shelf which was protected from the light and sunlight, and. Storage was carried out for one month. Determination of vitamin C levels in tablet was determined using Spectrophotometry UV-Vis method, then the results were statistically analyzed using One Way Anova. The results showed that the levels of vitamin C in the tablets on the front shelf, upper shelf, and lower shelf were 95,56%, 97,67%, and 98,95% respectively. The results exhibit the lowest level of vitamin C was found on front storage, nonetheless there was no significantly difference levels from all storage location.